2022
DOI: 10.1038/s41467-022-34195-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Food Compass with a healthy diet, cardiometabolic health, and mortality among U.S. adults, 1999–2018

Abstract: The Food Compass is a nutrient profiling system (NPS) to characterize the healthfulness of diverse foods, beverages and meals. In a nationally representative cohort of 47,999 U.S. adults, we validated a person’s individual Food Compass Score (i.FCS), ranging from 1 (least healthful) to 100 (most healthful) based on cumulative scores of items consumed, against: (a) the Healthy Eating Index (HEI) 2015; (b) clinical risk factors and health conditions; and (c) all-cause mortality. Nationally, the mean (SD) of i.FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
1
21
2
Order By: Relevance
“…It also discriminates between ultra‐processed products such as hot dogs and soft drinks from those such as packaged spaghetti sauce and whole grain, low‐sugar breakfast cereals (Mozaffarian et al., 2021). The Food Compass is also highly predictive of health outcomes and total mortality (O'Hearn et al., 2022). Further research is needed to explore the comparative health benefits of such approaches, as well as their feasibility for front‐of‐pack labelling purposes.…”
Section: Discussionmentioning
confidence: 99%
“…It also discriminates between ultra‐processed products such as hot dogs and soft drinks from those such as packaged spaghetti sauce and whole grain, low‐sugar breakfast cereals (Mozaffarian et al., 2021). The Food Compass is also highly predictive of health outcomes and total mortality (O'Hearn et al., 2022). Further research is needed to explore the comparative health benefits of such approaches, as well as their feasibility for front‐of‐pack labelling purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns are defined as the quantities, proportions, variety, or combination of different foods, drinks, and nutrients (when available) in diets, and the frequency with which they are habitually consumed. 18 Over the past two decades, many different sources and scientifically supported empirical or commercial dietary patterns have been widespread and have inspired a great deal of scientific research related to CMD, 19 , 20 , 21 such as the Mediterranean diet, vegetarian diet, dietary approaches to stop hypertension (DASH) diet, ketogenic diet (KD), etc. 22 , 23 , 24 Current evidence suggests that healthy dietary patterns are the most promising interventions for improving symptoms and reducing the risk of CMD.…”
Section: Introductionmentioning
confidence: 99%
“…Such statistical studies provide further evidence for the close relationship between these systemic diseases and periodontitis. Patients with these systemic diseases receive instruction in regard to their dietary habits [ 30 , 31 , 32 , 33 ]; therefore, these instructions may influence the association between periodontal parameters and nutritional factors. However, our previous study demonstrated that the frequency of yogurt and dark green vegetable consumption had positive effects on periodontal stabilization [ 18 ].…”
Section: Introductionmentioning
confidence: 99%